Strengthening Nepal’s Soft Power through Local Government Initiatives: People-to-people and Sister City Ties - Timilsana, Binod Khanda (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2025)
This study aims to explore the efforts of local government of Nepal that persuading global powers towards Nepal by strengthening soft power through initiatives like sister city ties and visit Bharatpur campaign within bilateral relations. By analyzing the network environment of people-to-people relations and Sister-City ties established by Bharatpur Metropolitan City of Nepal, this study seeks to extract creations, dynamics, and intricacies of local-level relations in terms of soft power and public diplomacy. Besides, this study discusses the city diplomacy and people-to-people connection initiatives created opportunities and its role in economy and tourism promotion. Initiatives of Bharatpur like establishing Sister-city relations and visit campaigns are analyzed as crucial soft power efforts by means of cultural exchanges, collaborations, partnerships, and public diplomacy linked to international relations of Nepal a like Japan in this study. Using qualitative approach based on empirical secondary data and propulsive method, this study has tried to answers how initiatives of Bharatpur impacting Nepal’s image in people-to-people ties at micro-level in cities like Japan. In addition, aspects of Nepal’s soft power resources and instruments linked to public and tourism diplomacy are studied. To understand the research findings soft power and public diplomacy perspectives in bilateral relations with reference to soft power superpowers Japan and small power Nepal is used as reference. Findings suggest that the local soft power efforts like Sister-City Relations and Visit Bharatpur 2024 campaigns remain as key soft power initiatives that leverage the economic activities, tourism promotion and cultural exchanges in grass-root level in bilateral relations.